Tolerance Re-Shaped in the Early-Modern Mediterranean Borderlands - Tagliaferri, Filomena Viviana, author.
1 online resource (234 pages)
Keywords: This book explores perceptions of toleration and self-identity through an analysis of otherness’ real experience of Italian travellers, Catholic missionaries and Maltese proto-journalists within Mediterranean border-spaces. Employing a multidisciplinary approach, which integrates the analysis of original and unpublished archival documentation with early modern European travel literature, the book shows how fluid subjects and border groups adapted to new environments, often generating information that made the Ottomans and their system of values real and dignified to an Italian audience. The interdisciplinary combining of historical methodology with the tools of comparative literature, anthropology and folklore studies provides a fresh perspective on concepts of tolerance as experienced in the early modern Mediterranean.